LEXICAL OPPORTUNITIES IN ENGLISH THROUGH THE LENS OF ETYMOLOGY - Ibrahim Halil Topal (IAIN Syekh Nurjati Cirebon, 2023)
A substantial linguistic base requires a good command of grammar and vocabulary. As Nation (2001) narrates, the knowledge of vocabulary encompasses form, meaning, and use. Aside from pronunciation and grammatical functions, etymology might also be associated with vocabulary knowledge (i.e., form and meaning) in that the spelling and pronunciation and, accordingly, meaning of words have evolved in time. In this regard, studying etymology might offer educational advantages for language learners and teachers. To this end, this study dealt with the utilization of etymology in vocabulary instruction. The background information and the conceptual framework of etymology were initially presented. The relationship of etymology with vocabulary and its significance were established next. Previous studies on the relevant topic were cited afterward. The potential benefits of etymology in language education, particularly vocabulary instruction, and their implications were discussed. The study concluded by verbalizing the limitations and offering recommendations for future research.